48 Trends in stage-specific breast cancer incidence in new south wales, australia: insights from 25 years of screening mammography. (20th August 2018) - Jacklyn, Gemma; McGeechan, Kevin; Irwig, Les; Houssami, Nehmat; Morrell, Stephen; Bell, Katy; Barratt, Alexandra
Abstract : Objectives: Screening mammography aims to improve breast cancer (BC) prognosis by increasing the incidence of early-stage tumours in order to decrease the incidence of late-stage cancer, but no reports have investigated these potential effects in an Australian population. Therefore, we aim to describe temporal trends in the incidence of stage-specific breast cancer in New South Wales, Australia, between 1972 and 2012. Method: An observational study of all women who received a diagnosis of BC from 1972–2012 as recorded in the NSW Cancer Registry, a population-based registry with almost complete coverage and high rates of histological verification. We analysed trends in stage-specific incidence before screening and compared them to periods after screening began. Our primary group of interest was women in the target age range of 50–69 years, though trends in women outside the target age were also assessed. Results: Screening was not associated with lower incidence of late-stage BC at diagnosis. Incidence for all stages remained higher than prescreening levels. In women aged 50–69 years, the incidence of carcinoma in situ (CIS), localised and regional BC has more than doubled compared to the prescreening era, with incidence rate ratios ranging from 2.0 for regional (95% CI 1.95 to 2.13) to 121.8 for CIS (95% CI 82.58 to 179.72). Before the introduction of screening there was a downward trend in distant metastatic BC incidence, and after the introduction of screening there was an increase (IRR 1.8; 95% CI 1.62 to 2.00). In women too young to screen the incidence of late-stage BC at diagnosis also increased, whereas localised disease was stable. Conclusions: The incidence of all stages of BC has increased over the past forty years, with the greatest rise seen during the established screening period for women aged 50–69 years. Our findings suggest that some of the expected benefits of screening may not have been realised and are consistent with overdiagnosis.